Late Holocene Human Impact on Tropical Soil Erosion in the Maritime Continent - Yanming Ruan; Mahyar Mohtadi; Lydie M. Dupont; Dierk Hebbeln; Sander van der Kaars; Wenwen Chen; Ellen C. Hopmans; Stefan Schouten; Matthias Prange; Jens Hefter; Gesine Mollenhauer; Enno Schefuß (Geophysical Research Letters)
Abstract Human activities have profoundly modified the fluxes in the global sediment cycle. However, the anthropogenic forcing on soil erosion beyond instrumental records or historical documentation is largely unknown. Here we analyze markers for low‐intensity fires and soil erosion in East Java over the past 5,000 years. We find evidence of a substantial human impact on fire occurrence due to the onset/intensification of swidden cultivation around 3,500 years ago, in the absence of changes in regional hydroclimate or vegetation. Highest soil erosion occurred during the past 500 years, coinciding with a transition toward permanent agriculture. Human‐impacted soil erosion was further amplified by intense monsoonal rainfall and strong rainfall seasonality around 2,000 and 300 years ago. With such rainfall anomalies projected to occur with higher frequency and severity in the tropics under the ongoing greenhouse warming, our results suggest an accelerating erosion rate in the future, posing risks for natural resources.